A conceptual model and detailed framework for stress-related, strain-related, and overuse athletic injury. Issue 8 (August 2020) - Kalkhoven, Judd T.; Watsford, Mark L.; Impellizzeri, Franco M.
Abstract: A multitude of athletic injuries occur when the various tissues that make up the human body experience stresses and strains that exceed their material strength. The precise amount of stress and strain that any given tissue can withstand is determined by the mechanical properties and resultant strength of that particular tissue. These mechanical properties are directly determined by an individual's physiology and acute regulation of these properties. A number of theoretical frameworks for athletic injury occurrence have been proposed, however, a detailed conceptual framework for injury aetiology that considers the interplay between the physiological and mechanical factors and outlines the causal pathways to tissue damage and injury is needed. This will guide injury research towards a more thorough investigation of causal mechanisms and understanding of risk factors. Further, it is important to take into account the considerable differences in loading patterns which can result in varying injury outcomes such as acute stress-related, strain-related, or overuse injury. Within this article a simplified conceptual model of athletic injury is proposed along with a detailed, evidence-informed, conceptual framework for athletic injury aetiology that focuses on stress-related, strain-related, and overuse injury.